BreakDancer: Identification of Genomic Structural Variation from Paired‐End Read Mapping. Issue 1 (21st March 2014) - Fan, Xian; Abbott, Travis E.; Larson, David; Chen, Ken
Abstract: The advent of next‐generation sequencing data has made it possible to cost‐effectively detect and characterize genomic variation in human genomes. Structural variation, including deletion, duplication, insertion, inversion, and translocation, is of great importance to human genetics due to its association with many genetic diseases. BreakDancer is a bioinformatics tool that relates paired‐end read alignments from a test genome to the reference genome for the purpose of comprehensively and accurately detecting various types of structural variation. Curr. Protoc. Bioinform . 45:15.6.1‐15.6.11. © 2014 by John Wiley & Sons, Inc.